An analytical study of the impact of steroid and drug use on the physical and mental health of students aged 18-20 years at the Faculty of Physical Education and Sports Sciences - Abdulhalim, Asst.L. Saleh Nayef; Karim, Asst.L. Taha Youssef; Mahmoud, L.Dr. Maan Hassan (Sulaimani Journal for Humanities, 2025)
This study aims to investigate the effects of performance-enhancing drugs and performance-enhancing substances on the physical and mental health of students aged 18-20 years old in the Colleges of Physical Education at Kirkuk University. The academic and athletic environment is witnessing increasing pressure to achieve high performance and athletic excellence, which leads some students to resort to using performance-enhancing drugs and performance-enhancing substances as a means to enhance their physical abilities and improve their performance quickly, despite the associated health and psychological risks. The research adopted a descriptive-analytical approach, collecting data from a final random sample of 400 male and female students, representing 75.4% of the original study population of 612 male and female students, after excluding a pilot sample (20) and invalid questionnaires (42). Researchers used a questionnaire designed to measure knowledge of the health and psychological risks, attitudes, and motivations for using performance-enhancing drugs, in addition to fitness measures and the POMS (Positive Mood Scorecard) (Thaer Sakban, 2017). The results showed that the level of awareness of the risks of using performance-enhancing drugs ranged from moderate to high, with significant differences between age groups and gender. Older students and females were more aware of the effects of these substances. Statistical analyses also revealed a positive correlation between the level of risk awareness and a negative attitude toward using performance-enhancing drugs, confirming the importance of preventive intervention. The study indicates that some students adopt positive attitudes toward using performance-enhancing drugs to achieve quick athletic gains, despite being aware of the negative health and psychological consequences. Therefore, the study recommends implementing awareness campaigns and psychological and sports support programs in coordination with health and legal authorities, in addition to including the topic of anti-doping in school curricula to promote health awareness and prevent potential risks.
Keywords: Stimulants; drugs; physical health; mental health; prevention